Broadband optical modulators : science, technology, and applications - Chen, Antao; Murphy, Edmond J. (Boca Raton, FL. : CRC Press, 2012)
'This book provides a comprehensive overview of the state of the art in optical modulator science and technology. It covers fundamental topics such as the electro-optic effect in nonlinear optic crystals and semiconductors. It addresses the optical and electro-optic properties of relevant materials, including traditional single crystalline lithium niobate, silicon, and III-V compound semiconductors, as well as emerging materials such as electrooptic polymers and organic nonlinear optic crystals. For each type of modulator, the author discusses the factors important to modulator performance, typical modulator design, and fabrication'--
Includes bibliographical references and index.
Keywords: Light modulators; Optoelectronic devices